Tonsilar metastases of melanoma in an older person - De Oliveira Semenzati, Graziela [UNESP]; Da Silva Móz, Luis Eduardo [UNESP]; Weber, Silke Anna Theresa [UNESP]; Martins, Maira Garcia [UNESP]; Martins, Regina Helena Garcia [UNESP] (Oxford University Press (OUP), 2013)
We presented a rare case of metastasis of melanoma in palatine tonsils alerting healthcare professionals to this diagnose in black oral lesions. © The Author 2013. Published by Oxford University Press on behalf of the British Geriatrics Society. All rights reserved.
Keywords: Melanoma; Neoplasm metastasis; Older people; Tonsil; clindamycin; protein S 100; vimentin; aged; case report; central nervous system metastasis; computer assisted tomography; ENT examination; female; human; human tissue; immunohistochemistry; melanoma; palatine tonsil metastases; prescription; priority journal; rare disease; tonsil tumor; tonsillitis; tumor biopsy